Data Analysis Software Implementation of Wireless Locomotive Reconnection Based on Zlib - LI Tiebing; LEI Mansheng; LEI Zhifang; SHEN Hongping (机车电传动)
After TEC_TROMS, the synchronous control system of locomotive reconnection based on wireless communication, running in batches in Shenhua railway, an operation recorder was added to the system based on the Zlib to record the running states and analysis the faults. A data analysis software solution for the recorder was presented and implemented from software’s decompression algorithm, software architecture, data routing. With the application of the software, plenty of historical inertia problems was located and analyzed, which provide evidences for control optimization, improving system operation quality.